Trace-wire Tests - ERICE - Vincent, Abhay; Pervier, Marie Laure A.; Pervier, Hugo (Cranfield University, 2023)
This item contains the data from the trace-wire testing performed for the ERICE project. The following files are present within this item: 1) Labview files (x3) - ".lvm" format (to be read in MS Excel) 2) Video files (x3) - ".mkv" format 3) README txt file (x1) - explaining the headers for the labview data and the instrumentation involved. Test 1 refers to Aluminium sample Test 2 refers to Wearlon sample Test 3 refers to AA Fsmooth sample
Keywords: trace-wire; ice protection; Ice Adhesion Strength